A Self-Reinforcing Process on Sidewalk: A Case Study in Jatibaru Raya – Tanah Abang Sidewalk, Jakarta - Sulistya Indriani; Rossa Turpuk Gabe; Joko Adianto (International Journal of Built Environment and Scientific Research, 2019)
The focus of this study is to analyze a sidewalk as a pedestrian path, not only as a mean to reach or return from a destination but it can also produce activities such as a self-reinforcing process in a certain time. These activities are certainly triggered by the presence of various users and their perceptions based on the sidewalk context. The phenomenon can be seen along the sidewalk in Jalan Jatibaru Raya Tanah Abang, Jakarta, Indonesia. Its function as a transit and commercial area certainly influences the activities in the sidewalk. Thus, walking is not the only activity on the sidewalk. People do selling, buying, or waiting there. The methodology of this study is a detailed observation of the physical environment as the main factor of human gatherers. Then, pedestrians become the main reference for other actors to come and do activities on sidewalk of Jalan Jatibaru Raya, Tanah Abang, Jakarta, Indonesia. The result showed that the process of a self-reinforcing process in sidewalk happens when someone starts doing something, allowing a clear tendency for others to join, either participating or merely experience or see what others do. However, the interconnection between the actors is inseparable from activity, space and time.